Truecaller's Spam Call and SMS Blocking Solution for Surveillance on Social Media - Indriyani Indriyani; Paula Dewanti (IHSA Institute, 2022)
The advancement of technology and communication has been impressively rapid. That are where emerging cybercrime technologies were born. Cyberspace activities involve the use of Internet users. One of them is a frequent social media user, which allows for communication interactions to take place without the need for face-to-face meetings. The Internet and social media, in addition to having a positive impact on users, also have a negative impact. One of them is a type of crime that is currently prevalent, namely digital cybercrime, which is a crime committed by varied individuals in order to deceive the target using data/information from the victim's social media account. Furthermore, in the current era of the Covid-19 pandemic, many victims have received fraud, such as spam calls and SMS, from people who use various methods to persuade, usually using the victim's family as tactic and overdue in loan payments as trap, and the number of these victims is growing. This study used a comparative study to examine the effectiveness of the Truecaller application in assisting smartphone users who are disturbed by continuous terror by using calls and Spam SMS, as well as overcoming victims' concerns.